Digitalization of Arabic Language Textbook Based on Communicative Learning to Improve the Linguistic Competence of Madrasah Tsanawiyah Students - Moh. Buny Andaru Bahy; Moh. Ainin; Abdul Wahab Rosyidi; Aulia Rahman; Muhammad Syaifullah; Abdul Wahab Naf'an (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2024)
Boredom in learning Arabic often occurs among students due to the lack of variety in teaching methods. This phenomenon must be answered immediately by creating contemporary learning variations. This research aimed to develop a digital Arabic book for class VIII Madrasah Tsanawiyah based on communicative learning. This research is of the Research and Development (R&D) type with Borg and Gall development steps. After conducting a survey of student needs and carrying out the steps of development research, the researchers developed a digital Arabic book, available at https://amba.my.id/login. This digital book has been validated for suitability by two subject matter experts and one media design expert. In its implementation, this digital book is very interesting and easy for students to use, effectively reducing students' boredom while learning Arabic. Moreover, this digital book also effectively improves students' Arabic language skills.